Three Case Reports of Pediatric Collagenous Gastritis with Recurrent Iron Deficiency Anemia - Tae Hwan Kim; Sumin Yoo; In Hyuk Yoo (The Korean Society of Pediatric Hematology-Oncology, 2023)
Iron deficiency is the most common nutritional deficiency in children and adolescents. Pediatric collagenous gastritis (CG) is a rare gastrointestinal disorder. Abdominal pain associated with iron deficiency anemia (IDA) is a common clinical symptom. We present three cases of pediatric CG diagnosed during the treatment of recurrent IDA. During esophagogastroduodenoscopy (EGD), nodularity of the gastric corpus was observed, which is a characteristic finding in pediatric patients with CG. Although pediatric CG could not be diagnosed by general EGD biopsy and pathological examination, it was diagnosed after suspecting pediatric CG and performing appropriate diagnostic tests. We recommend EGD for pediatric patients with recurrent IDA, especially for those with gastrointestinal symptoms. Moreover, when performing EGD, conducting appropriate examinations for pediatric CG is necessary.